SUPPLY CHAIN AND PURCHASING BEHAVIOR OF HALAL CHICKEN MEAT - Arif Julianto Sri Nugroho; Roos Kities Andadari; Eric Kunto Aribowo (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2018)
The segment of Muslim consumers in Indonesia currently has a high sense of concern for the halal goods and services they consume. This consumer segment, in addition to wanting high-quality products, also demands that the products they consume comply with the rules set by Islamic law. This segment has a tendency to be able to recommend to other parties the products they perceive are halal, they even want to pay a more expensive price if there are no alternative products of the kind they perceive halal. Instead, they can provide incorrect information which results in a viral effect and leads to encouragement to boycott the consumption of goods and services. This study aimed to examine the effect of halal supply chain knowledge on Muslim and non-Muslim consumers on the motivation and purchasing behavior of halal chicken meat. The halal supply chain knowledge tested includes halal feed dimensions, halal slaughtering processes, halal storage and logistics, and halal packaging and logistics. The research was conducted with a quantitative approach through multivariate multiple regression statistical tests. The population in the study was all consumers of halal chicken meat in Klaten City. Sampling using purposive sampling as many as 102 respondents. The final stage of the study found the findings of the four antecedent variables, three supply chain knowledge variables in the form of halal slaughter process, halal storage and logistics and halal labeling packing had a significant influence on purchasing motivation. Halal slaughter process had the highest influence on consumers because the halal perception that is most familiar to them is the slaughter process. One variable had no significant influence in the form of halal feed. In the motivation variable, the findings of this dimension had a significant influence on behavior.===========================================================================================Rantai Pasok dan Perilaku Pembelian Daging Ayam Halal. Segmen konsumen muslim di Indonesia saat ini memiliki rasa kepedulian yang tinggi terhadap kehalalan barang dan jasa yang mereka konsumsi. Segmen konsumen ini selain menginginkan produk yang berkualitas juga menuntut produk yang mereka konsumsi mematuhi aturan-aturan yang ditetapkan oleh syariat Islam. Segmen ini memiliki kecenderungan bisa merekomendasikan ke pihak lain produk yang mereka persepsikan halal, bahkan mereka mau membayar dengan harga yang lebih mahal jika tidak terdapat alternatif produk sejenis yang mereka persepsikan halal. Sebaliknya, mereka dapat memberikan informasi yang tidak benar yang mengakibatkan efek viral dan berujung anjuran memboikot konsumsi barang dan jasa tersebut. Penelitian ini bertujuan menguji pengaruh pengetahuan rantai pasok halal pada konsumen muslim dan non-muslim terhadap motivasi dan perilaku pembelian daging ayam halal. Pengetahuan rantai pasok halal yang diuji meliputi dimensi halal pakan, halal proses penyembelihan, halal penyimpanan dan logistic, serta halal pengepakan dan logistik. Penelitian dilakukan dengan pendekatan kuantitatif melalui uji statistik multivariat regresi berganda. Populasi dalam penelitian adalah seluruh konsumen daging ayam halal di Klaten, Indonesia. Pengambilan sampel menggunakan purposive sampling sebanyak 102 responden. Tahap akhir penelitian diperoleh temuan dari empat variabel anteseden, tiga variabel pengetahuan rantai pasok berupa halal proses penyembelihan, halal penyimpanan dan logistik, serta halal pengepakan labelling berpengaruh signifikan terhadap motivasi pembelian. Halal proses penyembelihan memiliki pengaruh paling tinggi pada konsumen karena persepsi halal yang paling familiar bagi mereka adalah kegiatan proses penyembelihan. Satu variabel tidak berpengaruh signifikan berupa halal pakan. Pada variabel motivasi diperoleh temuan dimensi ini berpengaruh signifikan terhadap perilaku.